Pemanfaatan Media Sosial Instagram Sebagai Sarana Promosi Terhadap Keputusan Pembeli Karang Hias di PT Dirga Mega Cipta Bekasi Jawa Barat - Alfina Damayanti; Akmal Abdullah; Ilham Ilham (Student Research Journal, 2024)
The utilization of social media as a promotional tool provides a wide opportunity for sellers to present their products on the internet. This allows consumers to make purchasing decisions regarding the products they have chosen.This study aims to determine how the implementation of Instagram Social Media as a promotional tool and its impact on buyer decisions for Coral at PT Dirga Mega Cipta, Bekasi, West Java. The research method used is a case study in the form of a qualitative approach while the type of research is descriptive. The qualitative approach is focused on "Generating Theory, while the data collection methods used are observation, interview, and documentation methods. The results of this study show that PT Dirga Mega Cipta has utilized social media in its promotional activities where and interaction and measurement of the effectiveness of promotional content on Instagram has a role in shaping purchasing decisions, both in general consumer scenarios and in B2B business environments. Companies need to understand these dynamics to design more effective and measurable marketing strategies on the platform.